1982
DOI: 10.1111/j.2044-8279.1982.tb00825.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Science Word Meaning in the Classrooms of Two Different Countries: Scottish Integrated Science in Scotland and in Malaysia

Abstract: Summary.— Many Scottish and Malaysian children study introductory science using the same teaching materials. A Scottish and a Malay sample of 14‐year‐old schoolchildren have been tested using word association tests of the meaning of a selection of 14 science concept words from the first year of integrated science. The tests clearly distinguished between the two samples. The Malay children generally produced more associates than the Scottish children and their responses were more homogeneous. Sets of semantic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Word associations also allow insights in the structure and work of the human memory (Thomson and Tulving, 1970;Petrey, 1977). It also reveals the relationships between them, allows for cultural differentiation (Isa and Maskill, 1982), and identifies the development of cognitive structures in certain domains. He found a positive correlation between learners' problem solving performance and the number of associations related to the problems.…”
Section: Word Association Test (Wat)mentioning
confidence: 99%
“…Word associations also allow insights in the structure and work of the human memory (Thomson and Tulving, 1970;Petrey, 1977). It also reveals the relationships between them, allows for cultural differentiation (Isa and Maskill, 1982), and identifies the development of cognitive structures in certain domains. He found a positive correlation between learners' problem solving performance and the number of associations related to the problems.…”
Section: Word Association Test (Wat)mentioning
confidence: 99%
“…Research in the past few years (i.e., Kawasaki, ; Lee, ) reveals that many languages, including Japanese and Chinese, lack the vocabulary required for the precise identification of certain abstract scientific terms and concepts. Such deficiencies no doubt account for the increasing dominance of English as the world's leading MOI in science education, although it is still acknowledged that learning science through the medium of a second language constitutes a formidable task, one that involves the simultaneous mastery of science content and a new language (Isa & Maskill, ; Strevens, ). Okebukola, Owolabi, and Okebukola () also recently found that parental preferences play a major role in schools' choice of English as the MOI for science learning, with those preferring English strongly resistant to a change to home‐language instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comments made during interviews, for example, were often reminiscent of those recorded by Watts (1983); and the reversion to non-scientific meanings in written tests was similar to findings by Isa and Maskill (1982). The way in which pupils may use formal knowledge to answer one question and life-world knowledge for another has also been referred to by Champagne et al (1980), Gilbert et al (1982), and Viennot (1979).…”
Section: Resultsmentioning
confidence: 77%